Find the natural number k such that 2 k + 2 3 4 + 2 3 7 is the square of an integer n .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Nice! I didn't thought with that
Thanks for the approach.
nice solution
very nice approach
The square of a natural number n can be expressed as n 2 . We need to find the value of k such that 2 k + 2 3 4 + 2 3 7 can be expressed as n 2 . 2 k + 2 3 4 + 2 3 7 = 2 k + 2 3 4 ( 1 + 2 3 ) = 2 k + 2 3 4 ( 1 + 8 ) = 2 k + 2 3 4 ( 9 ) = 2 3 4 ( 2 k − 3 4 + 9 ) = ( 2 1 7 ) 2 ( 2 k − 3 4 + 9 ) Taking x = 2 1 7 , we get, = x 2 ( 2 k − 3 4 + 9 ) As, out of the two factors of n 2 , one can be expressed as a square, we simply need to find a value for k − 3 4 such that 2 k − 3 4 + 9 can be expressed as a square. We know that, 1 6 + 9 = 2 5 can be expressed as a square i.e. 5 2 . Thus,the value of 2 k − 3 4 = 1 6 ⇒ 2 k − 3 4 = 2 4 ⇒ k − 3 4 = 4 ⇒ k = 3 8 Thus the value of k is 3 8 .
But what if k ≤ 3 4 ?
Nice solution.. Pretty understandable..
Thanks Ankan.
I did the same
According to the theory, we have
2 k + 2 3 4 + 2 3 7 = n 2 ⇔ 2 k = n 2 − ( 3 . 2 1 7 ) 2
⇔ 2 k = ( n + 3 . 2 1 7 ) ( n − 3 . 2 1 7 )
Hence,
{ 2 a = n + 3 . 2 1 7 2 b = n − 3 . 2 1 7
in which a ; b ∈ N , k = a + b , a > b
⇒ 2 a − 2 b = 3 . 2 1 8 ⇔ 2 b ( 2 a − b − 1 ) = 3 . 2 1 8
2 a − b − 1 is odd so,
{ 2 a − b − 1 = 3 2 b = 2 1 8
⇒ b = 1 8 ; a = b + 2 = 2 0
Then k = 3 8 .
This solution is very similar to the intended one.
It is important to note that just finding the numerical answer does not count for a complete solution. It is a long-standing mathematical tradition that when solving a problem, you are not allowed to assume that the question is well-posed. In other words, just because the question implies that the number k you are looking for is unique does not guarantee that it actually is: the fact that the question is legitimate is not included in the givens. Not realizing that and stopping after k = 3 8 was found was the most common mistake. Several people went further and tried to prove that the solution is unique, but it is actually fairly hard to do rigorously. For example, it is not immediately obvious that k ≥ 3 4 .
We know that 2^k+2^{34}+2^{37}=n^2 .....1
so taking 2^{34} common from the equation 1
so,we get 2^{34}(2^{k-34}+1+8)
as 2^34 is perfect square of 2^17 .so n to be perfect integer,
(2^{k-34}+9)...2 equation 2 should also be prefect square root
so to see value of square root , we put value k\geq34 so we put value of k in equation 2, k=34 we get 10 which is not a perfect square root : : : : k=38 we get 25 which is a perfect square of 5
therefore value of k is 38
if this is the square of an integer so we can write the integer on this form [x+y]^2 we have 2^[34] that we can sqrt it to 2^[17] So our integer will be on this form [x + 2^[17] ]^2 = 2^k +2^[34] +2^[37] Note that 2^[37] is not perfect Square, so 2^[37] = 2^[18] * x x = 2^[19] 2^k = x^2 So 2^[38] = 2^k
Considere o produto notável (x+y)^2 = x^2 + 2xy +y^2. Como 2^37 não é quadrado perfeito, faça com que ele seja o termo 2xy do produto notável e que 2^34 seja o x^2, entao y deve ser 2^19 e y^2 deve ser 2^38.
We have 2 k + 2 3 4 + 2 3 7 = m 2 ⟹ 2 3 4 ( 2 k − 3 4 + 9 ) = m 2
Now 2 3 4 is a perfect square. This implies ( 2 k − 3 4 + 9 ) is a perfect square. So let ( 2 k − 3 4 + 9 ) = p 2 ⟹ 2 k − 3 4 = ( p − 3 ) ( p + 3 ) Now the only powers of 2 that differ by 6 are 2 and 8 . So we finally have 2 k − 3 4 = 2 4 ⟹ k = 3 6
2^{34}+2^{37}+2^k=2^{34}[1+2^3+C]=2^{34}[9+C] If only C=16 then it will be perfect square. 16=2^4 So 2^{38}=2^k k=38
Let k be a natural number such that
2^k + 2^{34} + 2^{37} = n^2
where, n is any integer
2^k + 2^{34} X ( 1 + 2^3 ) = n^2
2^k + ( 9 X 2^{34} ) = n^2
2^k + ( 3 X 2^{17} )^2 = n^2
2^k = n^2 - ( 3 X 2^{17} )^2
2^k = ( n + 3 X 2^{17} ) X ( n - 3 X 2^{17} )
Since, the right hand side must be having no prime other than 2 in its factorization, hence, we have to get rid of the '3' present. This can be done of n is of the form ( 2m - 1) X 2^{17} as odd - odd = even.
The only 'm' satisfying this is m = 2 as for m=0,1 the expression will be negative, which is not possible while for m>2 other primes addition to 2 will come.
Hence, after putting n = 5 X 2^{17} in the equation,
2^k = ( 8 X 2^{17} ) X ( 2 X 2^{17} )
2^k = 2^{38}
=> k = 38
"Since, the right hand side must be having no prime other than 2 in its factorization, hence, we have to get rid of the '3' present. This can be done of n is of the form ( 2m - 1) X 2^{17} as odd - odd = even.
The only 'm' satisfying this is m = 2 as for m=0,1 the expression will be negative, which is not possible while for m>2 other primes addition to 2 will come." This is not a rigorous argument.
Let a 0 and b 0 be numbers such that a 0 + b 0 = n . Now we want ( a 0 + b 0 ) 2 = a 0 2 + b 0 2 + 2 × a 0 × b 0 = 2 k + 2 3 4 + 2 3 7 It is easy to see that a 0 2 = 2 k , b 0 2 = 2 3 4 and 2 × a 0 × b 0 = 2 3 7 . So 2 × a 0 × b 0 = 2 3 7 = 2 × 2 k / 2 × 2 3 4 / 2 = 2 2 k + 1 8 = 2 3 7 Therefore 2 k + 1 8 = 3 7 and then k = 3 8
2 k + 2 3 4 + 2 3 7 = 2 k + 2 3 4 ( 1 + 2 3 ) = 2 k + 2 3 4 ( 3 2 )
Assuming that k > 3 4 , 2 k + 2 3 4 ( 3 2 ) = 2 3 4 ( 2 k − 3 4 ) + 2 3 4 ( 3 2 )
Since 3 4 is even, we can treat this as a pythagorean triple where ( 2 1 7 ⋅ 5 ) 2 = ( 2 1 7 ⋅ 4 ) 2 + ( 2 1 7 ⋅ 3 ) 2 = 2 3 4 ( 2 k − 3 4 ) + 2 3 4 ( 3 2 )
Now, by letting 2 3 4 ( 2 k − 3 4 ) = ( 2 1 7 ⋅ 4 ) 2 and solving for k , we get k = 3 8
2 k + 2 3 4 + 2 3 7
should be a perfect square
This equation is equal to
2 3 4 ( 2 k − 3 4 + 2 0 + 2 3 )
2 3 4 ( 2 k − 3 4 + 1 + 8 )
since 2 3 4 is already a perfect square
( 2 k − 3 4 + 1 + 8 ) should be a perfect square too
( 2 k − 3 4 + 9 = 2 5 )
( 2 4 + 9 = 2 5 )
so k − 3 4 = 4
k = 3 8
2 k + 2 3 4 + 2 3 7 = 2 3 4 × ( 9 + 2 k − 3 4 ) and 1 6 + 9 = 2 5 = 5 2 . But here we have only found the smallest such k , there may be other values of k such that 2 k + 2 3 4 + 2 3 7 is a perfect square.
<=> 2^k + 2^34 + 2^37 = 2^k + 2^34.(1 + 2^3) = n^2 <=> 2^k + 2^34 . 9 = n^2 <=> Because 2^34 and 9 is perfect square, so 2^k also is perfect square. We know if 25 = 9 + 16 and 2^34 become distributor number. So, 2^k = 2^p . 16 = 2^34. 16 => 2^k = 2^(34+4) = 2^38. Then, we have k = 38
2^{k}+2^{34}+2^{37}= 2^{34}(2^{k-34}+1+8) 2^{34} is an perfect square 2^{k-34}+9 should also perfect square k=38
N= 2^34(2^(k-34)+1+8) taking 2^34 common N=2^34(2^(k-34)+9) so for N to be a perfect square 2^(k-34)+9 should be perfect square for 2^(k-34)+9=25 k=38
Problem Loading...
Note Loading...
Set Loading...
Because for the Perfect Spuare formula ( a + b ) 2 = a 2 + 2 a b + b 2
So ,we need to make 2 k + 2 3 4 + 2 3 7 like a Perfect Square,
Thus, k = 1 9 × 2 = 3 8